Orientational order of one-patch colloidal particles in two dimensions - Iwashita, Yasutaka; Kimura, Yasuyuki (Soft matter, 2014)
We studied the orientational order of one-patch colloidal particles (Janus particles) in a close-packed monolayer. In an experiment on hemispherically patched particles, we realized a highly ordered zigzag stripe pattern by inducing directional growth of the pattern via a phase transition of the solvent. Upon spontaneous ordering by strengthening the inter-patch attraction, however, the particles are trapped in a poorly ordered zigzag pattern, illustrating the importance of controlling kinetics to attain a highly ordered state. The patch-size dependence of an equilibrium orientational order is experimentally observed under moderate inter-patch attraction. We also calculated the equilibrium order against the patch size and attraction in a Monte Carlo simulation. In the simulation, the rather discrete transition between a zigzag stripe, tiling of triangular trimers and tiling of dimers under strong attraction becomes continuous with weakening attraction. The experimental result not only coincides with the simulation qualitatively but also suggests that a particular cluster is selectively formed by nonuniform inter-patch attraction in the experiment. The effect of patch-substrate attraction and commonalities of the order with liquid crystals are also discussed.